Development of Environmental and Technology Literacy-Oriented Science Comics as a Learning Media on Environmental Pollution - Azis, Gunawan; Hamidah, Ida; Amprasto, Amprasto (FKIP Universitas Lampung, 2022)
Learning media in schools has provided added value in the teaching and learning process. Science textbooks are not enough to achieve ideal learning. One of them is to use comics which can be said to be a pretty good visual medium. The purpose of this research is to produce an edutainment-based comic learning media that can improve students' environmental literacy and technological literacy. This study uses a research and development model (ADDIE). Researchers used data collection techniques by means of observation, interviews, documentation, questionnaires and tests. The data is processed so that it can improve students' environmental literacy and technological literacy on environmental pollution materials. The subjects in this study were seventh grade students of the Bandung National Junior High School. The instrument used for data collection in this study was a test of environmental literacy and technological literacy. The data analysis technique used mixed type qualitative methods and at the time of product field testing with quantitative methods. In the form of assessments of material experts and media experts, attractiveness questionnaires and class test results. Keywords: comic media, edutainment science, environmental literacy, technology literacy and environmental pollution. DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp734-743